STATIC STIFFNESS MODELING AND SENSITIVITY ANALYSIS OF SHIELD PROPULSION SYSTEM BASED ON VIRTUAL DISPLACEMENT PRINCIPLE - XU YouNan; SHI ZiQuan; HE Liu; CHU Hang (Jixie qiangdu)
Propulsion system is an important part of shield machine, and its stiffness will affect the propelling and steering function. In order to obtain the effective parameterized stiffness model of shield propulsion system, and to accurately describe the static stiffness of shield propulsion system in the whole working space, the static stiffness modeling method is studied. The physical model of shield propulsion system was established and its movement and force were analyzed. The stiffness model of shield propulsion cylinder was established by material mechanics formula and the relation between deformation of the end of themechanism in each direction and force or moment was constructed based on the principle of virtual displacement. The calculation formula of total stiffness matrix of shield propulsion system was obtained by superposition principle. The accuracy of the static stiffness model was verified by finite element method and its sensitivity was analyzed. It provides theoretical basis for structural design optimization and research analysis of shield propulsion system.